Analytical solutions for the forced KdV equation with variable coefficients - Wang, Ji; Fu, Jia; Dai, Jialin (Frontiers in Physics, 2025)
This paper focuses on obtaining the exact solutions to the variable-coefficient forced Korteweg-de Vries (KdV) equation for modeling spatial inhomogeneity in fluids. By combining the direct similarity reduction-based CK method with the (G'/G) expansion method, three new similarity solutions are obtained for this variable-coefficient forced KdV equation.